Siskiyou Trail [large type] - Rundell, B. N. (Rundell, B. N. Mccain chronicles, 2025)
"Amidst the growing chaos of the post Civil War America, former Union Colonel Elijah McCain is on a mission to find his deserter stepsons. Going through more struggles than he thought possible--maybe more than when he was a colonel in the war--McCain finally locates his stepsons, only to have them flee the civilized East in favor of the adventurous West. When their reckless decisions begin to catch up with them and they're kidnapped and thrown aboard a clipper ship, McCain is forced into action in order to save them. As fate would have it, he finds himself traveling down the Siskiyou Trail, a path littered with Mexican banditos, lost Danish settlers, and a disgruntled tribe of displaced Native Americans. Despite the obstacles thrown in the path of this ruthlessly determined retired colonel, McCain gave his word, and he will allow nothing man, nature, or evil incarnate to keep him from fulfilling his promise."--